Governance, business, legal, and technology: Strategies for addressing volatility and gharar in Sharia capital markets - Istianah Zainal Asyiqin; Muhammad Dafa Auliarizky Onielda (Universitas Ahmad Dahlan, 2025)
Introduction to the Problem: This study explored the intertwined challenges of market volatility and gharar in Sharia capital markets, which jointly contribute to uncertainty and instability. Volatility and gharar are mutually reinforcing phenomena, while speculative behaviors such as margin trading and short selling intensify both factors, resulting in price distortions, obscured asset valuations, and reduced investor trust in Sharia-compliant instruments. Purpose/Study Objectives: The objective of this research is to examine the characteristics and legal dimensions of both volatility and gharar in Islamic capital markets, assess their collective impact on Sharia-compliant issuers, and propose integrated governance, legal, business, and technological strategies to mitigate associated risks and enhance market resilience. Design/Methodology/Approach: This study adopted a juridical-empirical-normative approach. The empirical aspect involved collecting and analyzing market data from the Indonesian Islamic capital market. At the same time, the normative analysis focused on evaluating regulatory instruments, including DSN-MUI Fatwa No. 80/2011 and OJK Regulation No. 15/POJK.04/2015, and within the context of Sharia principles and business law. Findings: The study finds that both gharar and market volatility contribute to structural weaknesses in Islamic capital markets. In addition, speculative trading practices amplify uncertainty and instability, demanding a regulatory response that limits such activities. Strengthening corporate governance, enhancing disclosure practices, and applying business law mechanisms are essential to risk mitigation. The study recommends future research into cross-border regulatory comparisons and the role of financial technology in improving market transparency and Sharia compliance. Paper Type: Research Article